CALCULATION OF THE FREQUENCY RESPONSE AND BANDWIDTH IN LOW NUMERICAL APERTURE STEP-INDEX PLASTIC OPTICAL FIBER USING TIME-DEPENDENT POWER FLOW EQUATION - Drljača, Branko; Jovanović, Slavica; Savovic, Svetislav (Bulletin of Natural Sciences Research, 2016)
Time-dependent power flow equation is employed to calculate frequency response and bandwidth of low numerical aperture step-index optical fiber excited with Gaussian-like light source with large width. Both, frequency response and bandwidth, are specified as function of the fiber length measured from the input end of the fiber. Analytical and numerical solutions are compared and good agreement between results is obtained.